Mechanistic Understanding of Oxidation of Tin‐based Perovskite Solar Cells and Mitigation Strategies - Zhang, Zhihao; Huang, Yuanfang; Jin, Jialun; Jiang, Yiting; Xu, Yuliang; Zhu, Jingwei; Zhao, Dewei (Angewandte Chemie International Edition, 2023)
Tin (Sn)‐based perovskites as the most promising absorber materials for lead‐free perovskite solar cells (PSCs) have achieved the record efficiency of over 14 %. Although suppressing the oxidation of Sn‐based perovskites is a frequently concerned topic for Sn‐based PSCs, many studies have given vague explanations and the mechanisms are still under debate. This is in principal due to the lack of an in‐depth understanding of various and complex intrinsic and extrinsic factors causing the oxidation process. In this context, we critically review the chemical mechanism of facile oxidation of Sn‐based perovskites and differentiate its detrimental effects at material‐ and device‐level. More importantly, we classify and introduce the intrinsic factors (raw materials and solvent of perovskite precursors) and extrinsic factors (exposure to neutral oxygen and superoxide) causing the oxidation with their corresponding anti‐oxidation improvement methods. The presented comprehensive understanding and prospect of the oxidation provide insightful guidance for suppressing the oxidation in Sn‐based PSCs “from the beginning to the end”.